Lembaga Adat di Daerah Aliran Sungai Singingi - Adlin; Ali Yusri (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2019)
The existence of adat institutions is recognized in the government system of the Unitary Republic of Indonesia. This includes traditional institutions that exist at the village level. In the regulation of the Minister of Home Affairs No. 18 of 2018 concerning Village Social Institutions and Village Adat Institutions, it is stated that the village customary institution or other designation is an institution that carries out the customs function and forms part of the original arrangement of the village that grows and develops on the initiative of the village community. Singingi River Basin Formerly a kingdom called the Singingi kingdom which has a complete structure down to the country or village under its shelter. An interesting phenomenon is that the king in the Singingi River Basin is held by two people who have the title Datuk Khalifah. This study aims to explain history so that the emergence of two kings in the Singingi sect and describe the structure of traditional institutions in the country under its aegis. The theory used is the Geneological-Territorial customary law community alliance theory. The study used a qualitative method with the documentation method and was strengthened by conducting interviews with 8 informants and then analyzed through data triangulation. The research findings show that the Singingi river basin was formed based on geneological and territorial ties. The structure of adat institutions in each country modeled on the structure of adat institutions at the center of the kingdom, although there were variations in the application in each country.